2011
DOI: 10.3354/meps09264
|View full text |Cite
|
Sign up to set email alerts
|

Habitat type and schooling interactively determine refuge-seeking behavior in a coral reef fish throughout ontogeny

Abstract: Habitat selection by coral reef fish is influenced by a variety of biological and abiotic factors, but the relative importance of these factors is expected to change throughout ontogeny, especially for species that utilize different habitats during their life cycle. In this study, 2 in situ choice experiments were designed to test the individual as well as the interactive effects of habitat structure and schooling (with conspecifics or heterospecifics) on refuge-seeking behavior of a coral reef fish. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…However, our data show that mangroves were also frequently used by large individuals, suggesting that this habitat also provides some benefit to older, adult fish. This benefit can be related to the structural complexity of mangroves (Huijbers et al 2011), yet in our study, mangroves at Mbegani had higher food abundance than the adjacent seagrass beds, and growth rates were higher in mangroves than the seagrass beds for all size classes of L. fulviflamma. Thus, overlap in mangrove habitat use by juvenile and adults in our study area might also be facilitated by high food abundances that enhanced somatic growth.…”
Section: Discussionmentioning
confidence: 68%
“…However, our data show that mangroves were also frequently used by large individuals, suggesting that this habitat also provides some benefit to older, adult fish. This benefit can be related to the structural complexity of mangroves (Huijbers et al 2011), yet in our study, mangroves at Mbegani had higher food abundance than the adjacent seagrass beds, and growth rates were higher in mangroves than the seagrass beds for all size classes of L. fulviflamma. Thus, overlap in mangrove habitat use by juvenile and adults in our study area might also be facilitated by high food abundances that enhanced somatic growth.…”
Section: Discussionmentioning
confidence: 68%
“…6). Other studies have similarly found that species with a propensity for shoaling are more likely to seek shelter or structurally complex habitats when there are few or no conspecifics nearby (Huijbers et al, 2011;Magurran andPitcher, 1983, 1987). Both sheltering and group living can reduce predation risk (Almany, 2004;Magurran, 1990;Pavlov and Kasumyan, 2000;Pitcher and Parrish, 1993;Shulman, 1985), and numerous predators are found in Lwamunda Swamp, including piscivorous birds, fish, snakes, and aquatic insects (Chapman et al, 1996;Randle and Chapman, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…While sound and chemical cues can produce gradients on large spatial scales (kilometers), visual cues are useful only at small distances (a few meters) (Kingsford et al 2002, Leis andMcCormick 2002). Besides cues emitted by habitats, conspecifics and heterospecifics also provide cues to which animals can respond (Gebauer et al 2002, Lecchini et al 2005Huijbers et al 2011). Since different cues operate over different spatial scales and habitat requirements change with ontogeny, sensory preferences of animals may adapt according to their life stage and local sensory environments.…”
Section: Introductionmentioning
confidence: 99%